Ecofarming made easy - Muhunyu, Samuel (Technical Centre for Agricultural and Rural Cooperation, 2006)
Samuel Muhunyu, NGO official: Spore is an inspiring publication for me. In many instances it has triggered thought process in a direction I had not considered before,